PERMASALAHAN PERTIMBANGAN HAKIM MAHKAMAH KONSTITUSI TERKAIT LEGAL STANDING PEMOHON BERDASARKAN PUTUSAN NOMOR 90/PUU-XXI/2023: Issues Considered by Constitutional Court Judges Regarding the Petitioner's Legal Standing Based on Decision Number 90/PUU- XXI/2023 - Rayhan Putra Sena; Yogo Pamungkas (Faculty of Law, Trisakti University, 2024)
In submitting a request for judicial review, the applicant must explain the reasons for the applicant's request to litigate at the Constitutional Court. This is to determine whether the applicant has legal standing in a lawsuit at the Constitutional Court. In this research, the object of research is the Constitutional Court decision number 90/PUU-XXI/2023. In this decision the applicant felt disadvantaged by the enactment of Article 169 letter q of the General Election Law. And the judge's considerations in accepting the applicant's legal position are discussed in this research. So the formulation of the problem that will be discussed is whether the judge's considerations regarding the applicant's legal standing are in accordance with statutory regulations. This research uses an exploratory type of normative research using secondary data which is analyzed qualitatively by drawing conclusions using a deductive method. The conclusion of this research is that the Constitutional Court should not grant Legal Standing to the applicant to litigate because the applicant does not have urgent interests and does not feel any real loss. This is supported by dissenting opinions from several Constitutional Justices such as Saldi Isra, Suhartoyo, and Wahiduddin Adams as well as statutory regulations that regulate this matter.